PERILAKU TENAGA PENDIDIK DALAM PERKEMBANGAN PESERTA DIDIK - Muldiah, Siti (Jurnal Ilmiah Pendidikan dan Keislaman, 2024)
Lecturers need to adapt their teaching methods and styles so that students can understand the lessons correctly and well. In this method, lecturers can try using various teaching methods, such as active, collaborative and integrative learning. Social behavior is actions related to all actions that are directly related or linked to the social values ​​that exist in society. To be able to change behavior or morals in humans, it can be done by taking the path of habituation which is continuously implemented. Behavior is not something that is only studied within the scope of education, but behavior can also be realized in a person's personality so that it manifests good morals. Student development is the most real side which includes diversity in development, especially in the world of education. On campus and in society it is part of a complex social structure, which allows it to engage in cooperation and competition. This research uses qualitative methods. Qualitative research is collecting data in a natural setting with the aim of interpreting phenomena that occur where the researcher is the key instrument